Art and devotions to the Passion of Christ in Ireland, 1450-1650 - Connaughton, Jill Meghan (Trinity College (Dublin, Ireland). Department of History of Art and Architecture, 2012)
Passion devotion was an important element of the spiritual lives of the Irish Catholics who lived between the years 1450 and 1650. This interdisciplinary study explores the possible interpretations and uses of devotional art work related to the Passion of Christ in Ireland during this period. By not only considering the art but also elements of contemporary history, bardic poetry, and devotional literature, a deeper understanding of the meanings and uses that the devotional art of the Passion had for the people who encountered it and had it made has been developed in this study.
Keywords: History of Art, Ph.D.; Ph.D. Trinity College Dublin